Iron deficiency in patients with heart failure with mid-range and preserved ejection fraction - Morgado, Diogo Jácome (2020)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2019